Shannon Talian: capstone - Talian, Shannon, artist (Colorado State University. Libraries, 2013)
The artist's statement: Hans Christian Anderson once said, "Every man's life is a fairytale written by God's finger." If my created life is my own fairytale, then the works I create are the stories that fill up the book of my life. To me, all my artworks weave their own tales. Storytelling is the main conceptual drive behind most of my works and often the main inspiration for my creations. Personal experiences, legends, myth, fairytales, and superstitions all act as a jumping off point, but once the ground is left, wings of individuality spread and the object becomes unique unto itself. Just as every single person has a story to tell, objects weave tales also, waiting for someone to listen. Through imagery and material choice, I infuse symbolism and meaning into every one of my pieces. Each stone is carefully selected and each image is thus as well. There are no accidents, everything chosen has meaning. The initial origin of some works are blatantly clear, while others are hidden in layers of ambiguity; some tales have been told many times over, while others are coming to light in this world for the very first time. As with every story, details make it reveal character and plot, and I to wish to emulate this in my works as well. These narrations are meant to be enjoyed by those who wear them and by those who might catch a glimpse of them as they are displayed upon the human body. By using high end natural elements such as silver and copper, I am able to mold the metal into a product that whispers my foreseen vision. By using detail oriented techniques such as fabrication, lost wax casting, repoussé, enameling, and stone setting I am able to give each work a specific beauty that shines with quality and infuses the wearer with a certain elegance. I pour my soul into each creation, breathing a new, unique life into all I construct. Every work of mine is a story handcrafted with care making the journey just as important as the end result.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.